Controversial topics in metastatic HR+/HER2- breast cancer: Guiding treatment by a modified Delphi approach - Fabi, Alessandra; Buono, Giuseppe; Bria, Emilio; Bianchini, Giampaolo; Curigliano, Giuseppe; De Laurentiis, Michelino; De Placido, Sabino; Del Mastro, Lucia; Guarneri, Valentina; Generali, Daniele; Livi, Lorenzo; Lorusso, Vito; et al. (Frontiers in Oncology, 2022)
The treatment of HR+/HER2- metastatic breast cancer with cyclin-dependent kinases 4 and 6 inhibitors combined with endocrine therapy has recently emerged as the most relevant therapeutic strategy. However, in routine clinical practice, the best therapeutic approach in patients with comorbidities at early relapsing or ab initio metastatic disease, PI3K mutation, is still debated among oncologists. Given these areas of uncertainty, we conducted a Delphi survey to describe and confront the level of agreement or disagreement between clinicians working in referral vs local spoke oncological hospitals and summarize a consensus on these debated topics. In total, 56 items were drafted using the Nominal Group Technique and used for the Delphi Survey. A total of 46 clinicians participated in the survey. Overall, the consensus threshold among all participants was reached in 46/56 items (82%), and Delphi Survey results showed a high level of consensus. For the 10 items (18%) that did not reach the consensus threshold, possible explanations considering differences in clinical practice and recent findings from literature are provided in the Discussion. Outcomes from the present survey may help guide treatment in multiple comorbidities, early recurring and ab initio metastatic disease, and PI3K mutation, where evidence from randomized trials and level 1 evidence is currently missing.